Вплив поверхневої деформації на міцнісні властивості сталі 07Х12Н2МБФ - Мозговий, О.В.; Чепугов, О.П.; Тітов, А.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The influence of diamond burnishing on structural changes in on 07X12H2МБФ steel was researches by inner friction and micro hardness methods, that enabled to determine optimal regimes for finishing processing of surfaces.